2012
DOI: 10.1259/bjr/99567374
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between virtual cystoscopy image quality and CT slice thickness

Abstract: Objective: To investigate the effect of reconstruction slice thickness on image quality at CT virtual cystoscopy (VC). Methods: Pelvic CT examinations in bladder cancer patients were reconstructed at different slice thicknesses (0.6-5 mm) and intervals, and resulting VC images assessed. Quality indicators were ridging, holes, floaters and dimpling artefacts, tumour definition, and an overall score, ranked 1 (best) to 7 (worst). CT number and standard deviation (SD) for bladder contents and bladder wall were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, some studies revealed a noise-limited minimum thickness, such as the slice thickness of 1.2 mm superior to 0.6 mm because of increasing dimpling artifacts. 18 Similarly, the slice thickness with the range of 0.8–2 mm had no considerable impact on the residual setup error of stereotactic radiosurgery target localization. 19 In brain cancer, previous studies suggested 2.5 mm for tumor of <25 cm 3 in three-dimensional conformal radiation therapy and 1 or 2 mm in stereotactic body radiotherapy with small targets.…”
Section: Discussionmentioning
confidence: 90%
“…However, some studies revealed a noise-limited minimum thickness, such as the slice thickness of 1.2 mm superior to 0.6 mm because of increasing dimpling artifacts. 18 Similarly, the slice thickness with the range of 0.8–2 mm had no considerable impact on the residual setup error of stereotactic radiosurgery target localization. 19 In brain cancer, previous studies suggested 2.5 mm for tumor of <25 cm 3 in three-dimensional conformal radiation therapy and 1 or 2 mm in stereotactic body radiotherapy with small targets.…”
Section: Discussionmentioning
confidence: 90%
“…In our present study, we used 16-MDCT to perform urinary bladder scanning, with a section thickness of ∼1.25 mm and virtual reconstruction using a volume-rendering technique. Lalondrelle et al [6] suggested that the optimum slice thickness is 1.2 mm, as it usually results in the best image quality. On the other hand, decreasing the slice thickness (0.6 mm), leads to loss of tumour definition and results in appearance of dimpling artefacts due to increased noise.…”
Section: Discussionmentioning
confidence: 99%
“…Image noise is inversely relational with the variation square root in the beam thickness (slice thickness). Thinner slice thickness increases image noise [8]. Despite thinner slices increasing image noise, the visibility of a small lesion was improved by providing more diagnostic content [9].…”
Section: Effect Of Image Noise and Slice Thickness On Dect Imagesmentioning
confidence: 99%